2002
DOI: 10.1037/0022-0663.94.2.372
|View full text |Cite
|
Sign up to set email alerts
|

Home schooling and teaching style: Comparing the motivating styles of home school and public school teachers.

Abstract: The rapidly growing number of home schooled children in America creates a need for educators to understand the instructional dynamics of home schooling. The authors focus on the motivating styles teachers adopt in home school and public school contexts. Results showed that religiously motivated home educators embraced a relatively more controlling style than did public school teachers. Gender (being male) and frequent church attendance further predicted a preference to motivate children in controlling ways, ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 40 publications
2
19
0
2
Order By: Relevance
“…The use of pedagogic proposals in which teachers show an interpersonal style in their support of autonomy is essential, since when students that participate in classes characterized by a controlling teaching style are compared to those who attend classes based on support of autonomy, the latter exhibit better results in terms of greater participation during class, display more positive emotions, greater creativity, better information processing and conceptual understanding, and more persistence in the face of difficulties, among others (Cai, Reeve, & Robinson, 2002;Guay, Boggiano, & Vallerand, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The use of pedagogic proposals in which teachers show an interpersonal style in their support of autonomy is essential, since when students that participate in classes characterized by a controlling teaching style are compared to those who attend classes based on support of autonomy, the latter exhibit better results in terms of greater participation during class, display more positive emotions, greater creativity, better information processing and conceptual understanding, and more persistence in the face of difficulties, among others (Cai, Reeve, & Robinson, 2002;Guay, Boggiano, & Vallerand, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little attention has been paid to the personal characteristics of teachers that might affect their inclination to adopt a specific teaching style. The few studies that did consider personal characteristics, found support for the notions that the teachers' religiosity (Cai, Reeve, & Robinson, 2002), conservative political orientation (Reeve, Bolt, & Cai, 1999) and non‐self‐determination (Pelletier et al , 2002) relates to their embracing a more controlling teaching style.…”
mentioning
confidence: 99%
“…The results of the present study come to justify the view that EFL teachers tended to appreciate the students" efforts to work independently on the classroom level. Although this applies to the EFL teachers in the Turkish context, some teachers exhibit control-oriented teacher behaviors in the classroom setting regardless of autonomy supportive approaches (Cai, Reeve, & Robinson, 2002). In this respect, Reeve (2009) stated that teachers adopted a controlling motivating style because of cultural values and personal traits.…”
Section: Conclusion and Discussionmentioning
confidence: 96%